The Use of Code-Switching in The EFL Classroom of First-Grade At Junior High School - Mauliddiyah, Ainy; Munir, Ahmad; Mustofa, Ali (International Journal for Educational and Vocational Studies, 2020)
Code-Switching is not only find in social contexts, but we can also find it in the context of learning English in the class. Therefore, this research aims to observe the code switching which occurs in English class by students or a teacher. This research was conducted to find out in what context do code-switching take place in English class. The data in this study was analyzed qualitatively and through several stages. The study involved the students from class 7c who were able to make communication and also an English teacher in this class. The data is taken from the students’ and teacher's utterances and source data is taken from the result of the observation. Based on the data analysis, the results of this study indicated that code-switching occurred in several contexts. The most happened when there was making comment, another context was answering and asking questions, and also the context of opening discussion or conducting discussion activity.  In conclusions, From the data of the analysis showed that the use of code-witching in English class was success, because of the interaction of teachers who always encourage and help students by doing code-switching in certain contexts of the classroom.